Performance Evaluation of a MIMO based Underwater Communication System under Fading Conditions - Pranitha, B.; Anjaneyulu, L. (Engineering, Technology & Applied Science Research, 2019)
Due to the intense importance of underwater applications in military and commercial purposes, Underwater Acoustic Communication (UWAC) is an attracting research area. Very high propagation delay, path loss, and low bandwidth are the factors that challenged the acoustic waves in an underwater environment. Multi-input multi-output (MIMO) techniques are currently considered in UWAC to surpass the bandwidth limitation of the undersea channel. In this paper, the accomplishment of a MIMO in UWAC System highlighting both Line of Sight (LOS), i.e. the Rician fading and Non-Line of Sight (NLOS), i.e. the Rayleigh fading signal propagation, is assessed. Spatial Modulation technique is used, which helps in increasing the data rate in UWAC. It controls the spatial distribution of the energy caused by a signal in such a way that the single ocean channel sustains multiple parallel communication channels. The utilization of Zero Forcing (ZF) equalizer, which estimates the transmitted data proves the success of removing inter symbol interference (ISI). Matlab simulations are done for the UWAC system for values of LOS/NLOS. Because of various scattering effects in NLOS propagation, the error rate is considerably high when compared to that of the LOS propagation. Bit Error Rate (BER) values for the corresponding signal to noise ratio (SNR) are calculated.